High energy density asymmetric pseudocapacitors fabricated by graphene/carbon nanotube/MnO2 plus carbon nanotubes nanocomposites electrode - Hung, Chung Jung; Lin, Pang; Tseng, Tseung Yuen (My University, 2014)
Novel graphene/carbon nanotubes (CNTs)/manganese oxide (MnO2) nanocomposites plus CNTs (GMC + C) and graphene/CNTs hybrid (GC) thin-film electrodes are prepared by electrophoretic deposition (EPD). These nanocomposite electrodes exhibit high surface area and interconnected pore networks. The GMC + C nanocomposite electrode shows excellent specific capacitance of 964 F g(-1) at 1 A g (-1), rate capability with the residual capacitance of 529 F g(-1), at 500 mV s(-1), and fast Na+ diffusion with intercalation value of 6.34 x 10(-7) cm(2) s(-1), and deintercalation value of 8.86 x 10(-7) cm(2) s(-1). Such excellent pseudocapacitive performances are attributed to low ion/electron transport resistances and short ion/electron diffusion lengths. Furthermore, novel aqueous electrolyte-based asymmetric pseudocapacitor having 1.8 V cell voltage is successfully fabricated using GMC + C nanocomposite as a cathode and GC nanocomposite as an anode. The optimized asymmetric pseudocapacitor possesses superior performance with a maximum energy density of record high 304 Wh kg(-1) and retaining 56.2% of its initial specific energy density at the power density up to 242 kW kg(-1). In addition, the asymmetric cell configuration also shows excellent cycling stability with 89% specific capacitance maintained after 10,000 cycles. These results suggest that our designed asymmetric pseudocapacitors have a high potential for practical applications. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Graphene; Pseudocapacitor; Nanocomposite; Cycling stability